Impact of shift work on surgical outcomes at different times in patients with acute type A aortic dissection: A retrospective cohort study - Zhang, Xiang; Lv, Weiwei; Liu, Xin; Liu, Kai; Yang, Shaozhong (Frontiers in Cardiovascular Medicine, 2022)
Background To investigate the effect of shift work on surgical outcomes at different times in patients with acute type A aortic dissection (ATAAD). Materials and methods Patients with ATAAD who underwent total arch replacement at Qilu Hospital of Shandong University from January 2015 to March 2022 were retrospectively analyzed. All patients were managed according to the green channel emergency management strategy, and a professional cardiac team was arranged during off-hours. Based on surgery time and symptom onset to procedure time, the patients were divided into weekday, weekend and holiday groups; daytime and nighttime groups; intervention time ≤48 h and >48 h groups; working hours and off-hours groups. In-hospital mortality between these groups was compared. Results In total, 499 ATAAD patients underwent surgery within 7 days of symptom onset, and the in-hospital mortality rate was 10% (n = 50/499). Among the 499 patients, 320 (64.13%), 128 (25.65%) and 51 (10.22%) underwent surgery on weekdays, weekends and holidays, respectively. In-hospital mortality and 7-day mortality showed no significant difference among the three groups. Two hundred twenty-seven (45.5%) underwent daytime surgery, and 272 (54.5%) underwent nighttime surgery. Durations of ICU stay and hospital stay were significantly different between the two groups (P < 0.05). There was no significant differences in in-hospital mortality (9.2% vs. 10.7%) and 7-day mortality (4.4% vs. 6.6%). 221 patients (44.3%) and 278 patients (55.7%) were included in the intervention time ≤48 h and >48 h groups, respectively. Acute renal injury, ICU stay and hospital stay were significantly different (P < 0.05) whereas 7-day mortality (5.0% vs. 6.1%) and in-hospital mortality (8.6% vs. 11.1%) were not. Furthermore, 7-day (1.9% vs. 6.6%) and in-hospital mortality (11.1% vs. 9.8%) showed no difference between working hours group (n = 108) and off-hours group (n = 391). Cox regression analysis showed that postoperative acute renal injury (HR = 2.423; 95% CI, 1.214–4.834; P = 0.012), pneumonia (HR = 2.542; 95% CI, 1.186–5450; P = 0.016) and multiple organ dysfunction (HR = 11.200; 95% CI, 5.549–22.605; P = 0.001) were the main factors affecting hospital death in ATAAD patients. Conclusion Under the management of a professional cardiac surgery team with dedicated off-hours shifts, surgery time was not related to in-hospital mortality in ATAAD patients.